2003
DOI: 10.1542/peds.111.4.800
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori, Gastrointestinal Symptoms, and Metabolic Control in Young Type 1 Diabetes Mellitus Patients

Abstract: Amaç: Çalışmamızda diyabetiklerde dispepsi semptomları, semptom alt gruplarının organik ve fonksiyonel dispepsiyi ve spesifik tanıları ayırt etmedeki değerlerinin incelenmesi, Helicobacter pylori (H.pylori, HP) infeksiyonu ile spesifik dispepsi tipleri, semptomlar ve tanılar arasındaki ilişkinin incelenmesi, HP infeksiyonu ve histopatolojik tanılar, metabolik-klinik faktörler arasındaki ilişkinin incelenmesi amaçlanmıştır. Gereç ve Yöntemler: Tip 2 diyabetik 44 ve diyabetik olmayan 69 olgu çalışmaya alındı. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
4
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 22 publications
8
40
4
5
Order By: Relevance
“…This is in agreement with previous studies reported by Candelli et al [10], Anastasios et al [7], Demir et al [8] Xia et al [9], and Ko et al [11]. However, other studies reported a higher prevalence of H. pylori infection in type 2 diabetic patients in comparison to non diabetic subjects [12][13][14][15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous studies reported by Candelli et al [10], Anastasios et al [7], Demir et al [8] Xia et al [9], and Ko et al [11]. However, other studies reported a higher prevalence of H. pylori infection in type 2 diabetic patients in comparison to non diabetic subjects [12][13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…Community based surveys gave conflicting results about the prevalence of gastro-intestinal (GI) tract symptoms in persons with or without DM [5,6]. Some studies reported no difference in H. pylori infection rates between diabetic patients and controls [7][8][9][10][11], while other studies reported a higher rate of H. pylori infection in diabetic patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Whether Hp prevalence in young type 1 diabetes patients is higher than in the general population remains controversial [19][20][21]. Although not addressed in the present study, recent studies in Poland report a lower (∼16%) infection rate in healthy children [22].…”
Section: Discussionmentioning
confidence: 78%
“…However, evidence conflicts as to whether metabolic variables and levels of ghrelin were influenced by H pylori infection. [24][25][26] Candelli et al 25 showed that H pylori infection and cytotoxin-associated gene A-positive strains do not affect metabolic control in patients with type 1 diabetes mellitus. Gokcel et al 26 also reported that H pylori has no effect on plasma ghrelin concentration.…”
Section: Commentmentioning
confidence: 99%